Healthy gums does it matter? Amlodipine-induced gingival overgrowth (AIGO): a case report - Mohd Zainal, Abdul Zaki Ar Rasyid; Che' Man, Mohamad; Yatim, Yusnita; Abu Hassan, Nur Hafizah Ainaa (Universiti Kuala Lumpur (UniKL), 2025)
In Malaysia, more than half a million adults, representing 2.5% of the population, are living with four major non-communicable diseases (NCDs): diabetes, hypertension, hypercholesterolemia, and obesity. As for hypertension, 29.2% or 1 in 3 adults in Malaysia have hypertension, and 91% are on blood pressure medications. This includes dihydropyridine calcium channel blockers such as amlodipine, which is commonly used in primary care. We report a case from our primary care clinic involving a 70-year-old man with a known history of primary hypertension who developed painless gum swelling and discomfort while the patient was on T. amlodipine 10 mg. Oral examination showed diffuse gingival hypertrophy involving the upper and right lower gums. The condition resolved completely after discontinuation of the offending drug and substitution with an angiotensin-converting enzyme inhibitor. This case is notable because the gingival overgrowth developed only after 4 years of amlodipine 10 mg therapy. This paper aims to bring clinicians' attention to these adverse effects of amlodipine, so that timely and effective management can be given to the patient, avoiding complications and unnecessary treatment